Gambaran Penjualan Vitamin Pada Masa Pandemi Covid-19 di Kabupaten Bangkalan - Rizdyana Firmaniar; Yayuk Retnaningtyas (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background: The COVID-19 pandemic in 2021 is a major case where in January 2021 there was one of the highest peaks of positive cases. The virus can infect humans through airborne or droplet transmission. In that year there was also an increase in deaths due to COVID-19 infection. Therapeutic management for this disease requires antiviral drugs and vitamins. The purpose of this study is to determine the description of vitamin sales during the covid-19 pandemic. Method: This study uses a quantitative descriptive method with retrospective data collection. The sales data taken is data that occurred on January 1 - December 31, 2021 at Pharmacy